Optimization and selection of the multi-objective conceptual design scheme for considering product assembly, manufacturing and cost - Li, Congdong; Wu, Run; Yang, Weiming (SN applied sciences, 2022)
Conceptual design is the crucial stage of selecting and determining product composition and configuration, which greatly affects product performance and cost. In conceptual design stage, designers have the maximum design freedom in order to put forward to the optimal design solution in terms of assembly, manufacturing and cost. However, the above product aspects are analyzed independently in current industry, and a guided decision-making method based on multi-objective criteria is missing. Therefore, it is necessary to introduce a multi-objective analysis method to obtain an optimal conceptual scheme considering various aspects of product. Due to the complexity of product conceptual solution generation, this study divides the multi-objective analysis process into multi-objective solution optimization and multi-objective solution selection. The non-dominated solution set can be obtained from all the potential solutions in the former step. Then, the optimal conceptual solution can be obtained from the non-dominated solutions set in the latter step. The two-stage multi-objective analysis method has two advantages: (1) large dominated solutions can be quickly eliminated which can reduce the workload of solution selection; (2) TOPSIS method is easy to implement, which can work with attribute weights and scores of each design option. Finally, using the conceptual design of a centrifugal compressor as an example, the method's availability and practicality are demonstrated.